2020
DOI: 10.1007/s11571-020-09581-x
|View full text |Cite
|
Sign up to set email alerts
|

The successful discrimination of depression from EEG could be attributed to proper feature extraction and not to a particular classification method

Abstract: Reliable diagnosis of depressive disorder is essential for both optimal treatment and prevention of fatal outcomes. This study aimed to elucidate the effectiveness of two non-linear measures, Higuchi's Fractal Dimension (HFD) and Sample Entropy (SampEn), in detecting depressive disorders when applied on EEG. HFD and SampEn of EEG signals were used as features for seven machine learning algorithms including Multilayer Perceptron, Logistic Regression, Support Vector Machines with the linear and polynomial kernel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 65 publications
2
50
2
2
Order By: Relevance
“…At this point we should note that our intention was not to try to obtain the best possible classification performance by ''optimising'' the pre-processing of the raw fMRI data and/ or by trying to find the best set of graph-theoretic measures [other studies have already shed light towards this direction (Č ukić et al 2020;Xiang et al 2020;Vergara et al 2017)]. For example Č ukić et al (2020) showed that successful discrimination of depression from EEG could be attributed to proper feature extraction and not to a particular classification method.…”
Section: Discussionmentioning
confidence: 99%
“…At this point we should note that our intention was not to try to obtain the best possible classification performance by ''optimising'' the pre-processing of the raw fMRI data and/ or by trying to find the best set of graph-theoretic measures [other studies have already shed light towards this direction (Č ukić et al 2020;Xiang et al 2020;Vergara et al 2017)]. For example Č ukić et al (2020) showed that successful discrimination of depression from EEG could be attributed to proper feature extraction and not to a particular classification method.…”
Section: Discussionmentioning
confidence: 99%
“…In many studies on the diagnosis of depression and schizophrenia [88][89][90][91][92][93][94][95][96][97], the nonlinear EEG analysis have been reported, but no nonlinear EEG analysis with accuracy has been reported for comorbid psychotic disorders and depression in patients with epilepsy. Psychiatric comorbidities are common in patients with epilepsy [3], and associations for psychosis with the age at onset, duration of epilepsy, and seizure frequency have been reported.…”
Section: Comorbid Psychiatric Disordersmentioning
confidence: 99%
“…Milena Cukic [77] worked out that for effective therapy and to avoid tragic results, a reliable diagnosis of depressive illness is required. The main focus of this study was the performance of Higuchi's Fractal Dimension and Sample Entrop on EEG in diagnosing psychological illnesses.…”
Section: Literature Reviewmentioning
confidence: 99%